Та кырӟанъёсы-турагайёсы: люкам кылбуръёс, поэмаос / Куӟебай Герд ; дасяз Ф. К. Ермаков - Герд Кузебай (Удмуртия, 1994)
Экземпляры: (20230920) / Инвентарный номер: 25691 / Цена: 10.00 / Сис.шифр: 84(2=664.1) / Авт.знак: Г 37 / ГРНТИ: 17.82 / ББК: 84(2=664.1)